AN OVERVIEW OF SOME HERBAL ANTIDEPRESSANT PLANTS - PATIL, TANMAYI; KALE, MOHAN; KUMBHAR, RUTUJA; BODKE, VISHAL; CHAUDHARI, KOMAL (International Journal of Current Pharmaceutical Research, 2024)
There are numerous ways to categorize and treat depression, which is a diverse mood disease. The illness is caused by factors such as 5-HT, NA, and MAO-A inhibition and stimulation. Reduced curiosity about pleasure, feelings of inappropriate guilt or worthlessness, a drop in hunger and sexual desire, sleeplessness, and persistent suicidal thoughts are some of the symptoms. There are several synthetic medications used to treat depression, but not all of them make patients happy, and some of them may have negative side effects. Many have turned to well-liked traditional herbal remedies to avoid the negative effects of allopathic therapy. Due to their broad application, therapeutic efficacy, and little to negligible adverse effects, herbal medications are currently used worldwide. Several medicinal plants and medicines derived from these plants have shown antidepressant properties by the combined effect of their medicinal constituents. We discuss promising novel medicinal products targets for the management of major depressive illness in this review. We address the potential antidepressant benefits of selectively targeting receptors, including opioid, G-protein-coupled, and metabotropic glutamate receptors. Since they may also have therapeutic value, we also talk about substances that target biological processes, including inflammation, the gut microbiota, the cholesterol biosynthesis pathway, and the hypothalamic-pituitary-adrenal axis. Lastly, we offer a synopsis of all the plants displayed in graphical format, together with an overview of the antidepressant plants which currently are widely accessible.